A Study on Consumer Perception Towards Digital Payment - Prakash M (East Asian Journal of Multidisciplinary Research, 2022)
The digital economy, electronic commerce and electronic banking are now being used by the new technologies and the wider global network, especially internet, within and outwardly. Increasing use of internet, electronic devices and government initiative such as digital India with a vision to transforming India into digital society by cashless transaction. After demonetization in India the digital payment system emerged tremendously. In recent days many changes took place in the payment system like digital wallets, UPI, AEPS, QR code and BHIM apps for smooth shift to digital payments. The study investigates a customer’s perception towards Digital payments. The structured questionnaire was used as research tool for understanding consumer perception of digital payment. Primary data was collected from respondents in Ramanagara district and Bangalore district.